TINJAUAN YURIDIS PENEGAKAN HUKUM PIDANA KEKARANTINAAN KESEHATAN DALAM PENANGGULANGAN WABAH COVID-19 DI KOTA MEDAN - Martina Nurchani (Universitas Harapan Medan, 2022)
Law enforcement aims to improve order and legal certainty in society. As a form of efforts to achieve a comprehensive rule of law in law enforcement, especially when a certain virus outbreak or pandemic occurs, the Government together with the House of Representatives of the Republic of Indonesia. The role of the government and the community in the successful implementation of the Emergency Community Activity Restriction (PPKM) is in line with how the role is in the fulfillment of rights and obligations. The research method in this study is a normative legal approach. The main object is the norms or rules of positive legal rules that regulate criminal law policies as an effort to overcome the Covid-19 emergency. The criminal law enforcement process against perpetrators of health protocol violations in the city of Medan is in accordance with Law Number 6 of 2018 concerning Health Quarantine, however the government has not fully fulfilled the rights of the community during the implementation of large-scale social restrictions (PSBB) and the implementation of restrictions on community activities (PPKM). ). The role of the people of Medan City in dealing with Covid-19 and compliance with PPKM is still considered low. Based on data from the Medan City Government, the number of violations of the Covid-19 health protocol in Medan City is increasing. The latest data, from July 15 to August 09, 2021, as many as 52 people who violated health protocols (prokes) during Emergency PPKM and Level 4 PPKM in Medan City. The 52 people are non-essential, namely business actors and traders and have undergone a trial for minor crimes.